The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.4315/0362-028x-61.6.688
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Bacteriological Characteristics of Pichtogalo Chanion Cheese and Mesophilic Starter Cultures for Its Production

Abstract: Sixty-two samples of Pichtogalo Chanion cheese traditionally produced in Crete, a few (3 to 6) days old, were analyzed for some chemical and bacteriological characteristics. The results of physicochemical analyses were as follows: (1) moisture content 61.63% (standard deviation 4.67); (2) fat in dry matter 54.03% (SD 7.73); (3) protein content 14.23% (SD 1.72); (4) salt content 1.02% (SD 0.38); (5) water activity (aw) 0.990 (SD 0.003); and (6) pH 4.36 (SD 0.25). None of the samples yielded Salmonella spp. List… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 0 publications
2
14
0
3
Order By: Relevance
“…Also, the presence of P. aeruginosa and sulfite reducing clostridia would offer risk to public health, probably leading to contamination of cheese, with consequent reduction of shelf life. Sulfite reducing clostridia are able to produce enzymes that cause late swelling in cheeses (12,19,21). Pseudomonas aeruginosa also produces thermoresistant proteases and lipases that could alter organoleptic properties of the final product.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the presence of P. aeruginosa and sulfite reducing clostridia would offer risk to public health, probably leading to contamination of cheese, with consequent reduction of shelf life. Sulfite reducing clostridia are able to produce enzymes that cause late swelling in cheeses (12,19,21). Pseudomonas aeruginosa also produces thermoresistant proteases and lipases that could alter organoleptic properties of the final product.…”
Section: Resultsmentioning
confidence: 99%
“…These values were lower than those reported by Ashenafi (1990) in cottage cheeses, which was 10 7 cfu/g. Papageorgiu et al (1998) have found, in Pichtogalo Chanion cheese that yeast and mould counts were 10 6 and 10 4 cfu/g respectively.…”
Section: Discussionmentioning
confidence: 96%
“…Νωπά τυ ριά είναι και τα τυριά τυρογάλακτος όπως το Μανοΰρι, η νωπή Μυζήθρα, ο Ανθότυρος, το Riccotone, τα οποία ε ξετάζονται ξεχωριστά, καθώς και η Mozzarella (κεφ. 3.1.6), η οποία είναι ο εκπρόσωπος των τυριών τΰπου Pasta filata (Anifantakis, 1991;Kosokowski and Mistry, 1997;Papageorgiou et al, 1998 , σε ποσοστό 6,45% των δειγμάτων που εξετάστη καν (Papageorgiou et al, 1998).…”
Section: νωπά τυριάunclassified